Pengaruh Brand Love dan Brand Image di Mediasi oleh Customer Engagement Terhadap Customer Loyalty Konsumen Eiger Adventure - Rabbani, Muhammad Fajar (UNIB Press, 2024)
The purpose of this study was to determine the effect of brand love and brand image mediated by customer engagement on customer loyalty of Eiger Adventure consumers. This study uses a quantitative approach with a research design, namely a survey design. The data used are primary data obtained through the distribution of online questionnaires. The research population is Eiger consumers who buy Eiger products on Tokopedia and Shopee. The sampling technique uses non-probability sampling with a purposive sampling technique. The total sample in this study was 232 respondents. The data processing technique for this study uses PLS-SEM with the help of the SmartPls program with version 4.0.0. The tests conducted in this study are the outer model test, the inner model test, and the mediation effect test. The results of the study indicate that brand love and brand image have a positive and significant effect on customer engagement, customer engagement has a positive and significant effect on customer loyalty, brand love and brand image have a positive and significant effect on customer loyalty, brand love and brand image have a positive and significant effect on customer loyalty mediated by customer engagement. Keywords: customer loyalty, customer engagement, brand image, brand love